Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd008298.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Physical health care monitoring for people with serious mental illness

Abstract: Background Current guidance suggests that we should monitor the physical health of people with serious mental illness and there has been a significant financial investment over recent years to provide this. Objectives To assess the effectiveness of physical health monitoring as a means of reducing morbidity, mortality and reduction in quality of life in people with serious mental illness. Search methods We searched the Cochrane Schizophrenia Group Trials Register (October 2009) which is based on regular search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The use of psychotropic drugs like antipsychotics or mood stabilizers but also specific antidepressants further increases the risk of somatic complications as a result of, among others, drug-induced disturbances in metabolic parameters, liver function and ECG [ 6 , 8 , 23 , 24 ]. Although the effectiveness of somatic monitoring on treatment outcomes has not been well established [ 25 ], it seems logical to monitor these known somatic complications of mood and anxiety disorders and adverse effects of psychotropic drugs, especially in patients with a high prevalence or a high risk of morbidity or mortality [ 26 , 27 ]. Importantly, this low rate of monitoring is in contrast with the SMI patients’ perceived need to have their somatic health screened and monitored, as their ability to survey their own physical health interest is reduced [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of psychotropic drugs like antipsychotics or mood stabilizers but also specific antidepressants further increases the risk of somatic complications as a result of, among others, drug-induced disturbances in metabolic parameters, liver function and ECG [ 6 , 8 , 23 , 24 ]. Although the effectiveness of somatic monitoring on treatment outcomes has not been well established [ 25 ], it seems logical to monitor these known somatic complications of mood and anxiety disorders and adverse effects of psychotropic drugs, especially in patients with a high prevalence or a high risk of morbidity or mortality [ 26 , 27 ]. Importantly, this low rate of monitoring is in contrast with the SMI patients’ perceived need to have their somatic health screened and monitored, as their ability to survey their own physical health interest is reduced [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leitner et al (2008) carried out a systematic review and uncovered no less than 24 studies in this area. Given the plethora of papers advocating the importance of monitoring the physical health check of people with SMI, it is striking that both our attempt and that of Tosh et al (2010) to evaluate the evidence in this area by carrying out a systematic review, unearthed absolutely no studies. As more patients with SMI die from cardiovascular disease than suicide (Gray et al 2009), it is vital that researchers start to publish details of healthcare professional education and their outcomes in physical health and SMI research.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane Effective Practice and Organization Care Group Review (Tosh et al 2010) did not identify any randomized trials which assessed the effectiveness of physical health monitoring in people with SMI. They concluded that guidance is based on expert consensus, clinical experience and good intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Tosh et al (Tosh et al, 2010), working with the Cochrane Schizophrenia Group, evaluated all randomized or quasi-randomized clinical trials focusing upon physical health monitoring versus standard of care or comparing self-monitoring versus monitoring by a health professional or simple versus complex monitoring or specific versus non-specific checks or once only versus regular checks or comparison of different guidance. There were no studies that fulfilled the review criteria, so they could not evaluate the impact of health monitoring on quality of life.…”
Section: Discussionmentioning
confidence: 99%